Survey mode as a moderator of context effects - Doušak, May (Metodološki zvezki, 2017)
After decades of survey quality research and many experiments on the mode of data collection as a source of data inequivalence, there is still no exact explanation of how the mixed-mode design impacts the collected data. While not providing a definitive answer, we propose a new explanation of the mode effect and how it correlates with other sources of errors in surveys. By reviewing the relevant literature, we develop theoretical arguments indicating that the mode of data collection is in fact a moderator of context effects, a view that can provide an answer to the question concerning the origin of the data cacophony in mixed-mode comparative studies.
Keywords: Data collection; Družboslovne ankete; Social surveys; Zbiranje podatkov